Evaluation of the User Experience of Shopee and TikTok Shop Among Generation Z - Muhammad Galih Wonoseto; Dodi Saputro; Zahra Zakila Anindha Rahmanti; Eko Hadi Gunawan; Adriel Devara Sandji (Jurnal Sistem Informasi Bisnis, 2026)
Digital transformation has accelerated the emergence of social commerce, a business model that integrates social interaction with online transactions. Although Shopee and TikTok Shop are among the leading digital commerce platforms in Indonesia, empirical studies comparing their user experience among Generation Z remain limited. This study aims to compare the user experience of Shopee and TikTok Shop among Generation Z users in Indonesia using the User Experience Questionnaire (UEQ). A comparative quantitative approach was employed, involving 60 respondents aged 18–27 years, consisting of 30 Shopee users and 30 TikTok Shop users selected through purposive sampling. Data were analyzed using UEQ score calculation, benchmark analysis, and independent sample t-tests. The results show that TikTok Shop achieved higher mean scores across all UEQ dimensions, particularly in Dependability (+0.47) and Stimulation (+0.33). UEQ benchmark analysis classified most Shopee dimensions as Below Average, whereas all TikTok Shop dimensions were categorized as Above Average. However, no statistically significant differences were found between the two platforms (p > 0.05), indicating that both provide relatively comparable user experiences. The novelty of this study lies in its comparative evaluation of a conventional e-commerce platform and a social commerce platform using the UEQ framework within the context of Generation Z users in Indonesia. The findings contribute to the growing body of social commerce literature by providing empirical evidence regarding how entertainment-oriented features and social interaction mechanisms shape user experience perceptions. These insights may assist platform developers in designing more engaging and user-centered digital commerce experiences.